Disonansi Kognitif Gay Terkait Budaya Patrilineal di Bali - I Dewa Ayu Maythalia Joni; Hadi Sutarmanto (Faculty of Psychology, Universitas Gadjah Mada, 2017)
The research was purposed to know how cognitive dissonance of gay-related towards patrilineal culture in Bali. Subjects of this research were two Balinese born gay. Each of the subjects has two significant others. The subjects were selected by theory-based/operational construct sampling method to make sure that it represents the real phenomenon and compatible with the purpose of the research. The research used a qualitative method with phenomenology approach through an analysis model by Purwandari (2007). Method of the sampling was an interview with a list of questions based on the purpose of the research. The result showed that there was a different level of cognitive dissonance on both subjects. It was based on their own background and causes of cognitive dissonance. The research also showed that there was a different effort from each of the subject to solved cognitive dissonance.